The inï¬‚uence of corporate reputation on the quality corporate social responsibility disclosure: Banking sector - Andika Pramukti; Hamzah Ahmad; Nurina Saffanah (The Indonesian Accounting Review, 2022)
This study is aimed to examine the effect of reputation toward the quality of corporate social responsibility disclosure. This study applied an index based on the qualitative characteristics of the International Financial Reporting Standard Conceptual Framework. In addition, the study is modified with Â a measured variable of the Quality of Corporate Social responsibility Disclosure. Furthermore, this study used purposive judgment sampling and 13 relevant financial sector companies were obtained. The result indicates that company reputation has positive relationship with the quality of CSR disclosure, but it is insignificant. In addition, this study indicates that the relevant dimension has not been highlighted compared to other dimensions such as loyal representation, understanding, and Comparability. CSR disclosures prioritize quality in order to be credible communication tool for the users.